Vocal-Point Kebijakan: Praksis dalam Transformasi Klaster Tenun-Ikat Berbasis Kearifan Lokal dari Perspektif Ekofeminisme di Kabupaten Sumba Timur - Hunga, Arianti Ina Restiani (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
East Sumba Regency is included in the 3T area category (underdeveloped, isolated, and poorest). Covid-19 pandemic, flash floods, and Seroja hurricane are predicted to increase the worsening poverty. This condition encourages the pursuit internal strength to increase the community’s resilience. This paper describes two findings: 1) the praxis of focal point in the transformation of local wisdom-based tenun ikat (handwoven fabric) clusters from an ecofeminism perspective, and 2) best practices as the basis of integrating tenun ikat in the Regional Medium-Term Development Plan (Rencana Pembangunan Jangka Menengah Daerah/RPJMD) of East Sumba Regency. The paper uses several conceptual frameworks such as agent, agency, and agent network from an ecofeminism perspective. The research used the Participatory Action Research method from an ecofeminism perspective. The results show that the praxis of the focal point is significant in the transformation of local wisdom-based tenun ikat and the supervision of the integration of tenun ikat in policies implemented in the RPJMD of East Sumba Regency in 2021-2025.